The inflow performance relationship in fractured, vertical, and dewatered coalbed-methane wells - Dou, Xiangji; Lu, Jiahao; Li, Jingxuan; Wu, Xiaojun; Zhai, Yu; Wu, Bo; Qian, Kun (Frontiers in Earth Science, 2022)
The inflow performance relationship (IPR) of dewatered vertical coalbed methane (CBM) well is essential to the development of whole CBM reservoir, which was less studied. The dynamicity of stress sensitivity effect (SSE) and matrix shrinkage effect (MSE), and special hydraulic fracture propagation were all neglected. A novel IPR model was built by integrating dynamic SSE-MSE and hydraulic fracture propagation into skin factor, and was well validated by real production data from Qinshui Basin, China. The absolute open flow rate with SSE-MSE is 60.5% larger than the one without SSE-MSE. The MSE possesses larger effect on fracturing skin factor than SSE and tends to lower the fracturing skin factor, benefitting to the production of CBM well. Besides, with the consideration of SSE or MSE, the non-Darcy flow effect would be weaker due to the restraint of velocity of flow or the permeability. A useful and essential theoretical guidance to the real CBM production could be provided by this novel IPR model.